In‐Transit Electroextraction of Small‐Molecule Pharmaceuticals from Blood. Issue 12 (12th February 2019) - Nanthasurasak, Pavisara; See, Hong Heng; Zhang, Min; Guijt, Rosanne M.; Breadmore, Michael C.
Abstract: An electrokinetic platform was developed for extracting small‐molecule pharmaceuticals from a dried blood spot. Through the exclusion of liquid reagents and use of low field strength (6 V cm −1 ), the electroextraction of a drug from a dried blood spot, deposited on a polymer inclusion membrane (PIM), could be realised while in transit in the mail. In transit sample preparation provides a potential solution to in situ sample degradation and may accelerate the workflow upon arrival of a patient sample at the analytical facility. The electroextraction method was enabled through our discovery of the use of 15–20 μm thin PIMs as electrophoretic separation medium in absence of liquid reagents. Here, a PIM consisting of cellulose triacetate as polymer base, 2‐nitrophenyl octyl ether as plasticizer and 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide as carrier was used. The PIM, was packaged with two 12 V batteries to supply the separation voltage. A blood spot containing berberine chloride was deposited and dried before the applying the separation potential, allowing for the electroextraction while the packaged device was shipped in internal mail. Upon arrival in the analytical laboratory, the PIM was analysed using a fluorescence microscope with photon multiplier tube, quantifying the berberine extracted away from the sample matrix. This platform represents a new opportunity for processing clinical samples during transport to the laboratory, saving time and manual handling to accelerate the time to result. Abstract : Mail service : An electrokinetic platform was developed for extracting small‐molecule pharmaceuticals from a dried blood spot. Through the exclusion of liquid reagents and use of low field strength, the electroextraction of a drug from a dried blood spot, deposited on a polymer inclusion membrane, could be realised while in transit in the mail.